Risk for CMV reactivation in children undergoing allogeneic hematopoietic stem cell transplantation. Issue 2 (27th September 2014) - Qayed, Muna; Khurana, Monica; Hilinski, Joseph; Gillespie, Scott; McCracken, Courtney; Applegate, Kristy; Chiang, Kuang‐Yueh; Horan, John
<x xml:space="preserve">Abstract</x> Tailoring pre‐emptive CMV therapy to hematopoietic cell transplant recipients' risk for reactivation could make this approach more cost‐effective. To determine the feasibility of creating a risk classification system for this purpose, we analyzed 169 pediatric HCTs involving seropositive recipients or donors. Using risk factors derived from multivariable analysis, we stratified patients as having no risk factors, any one, any two, or all three risk factors (age, donor type, and presence of GVHD). The cumulative incidence of reactivation was 4.7%, 10.1%, 21.1%, and 40.9%, respectively (P ≤ 0.001). These results demonstrate the feasibility of creating a risk classification schema. Pediatr Blood Cancer 2015;62:364–366. © 2014 Wiley Periodicals, Inc.